First-Principles Calculations of Electronic, Elastic and Thermal Properties of Magnesium Doped with Alloying Elements - 杨晓敏;赵宇宏;HOU Hua;ZHENG Shuhua;HAN Peide (Journal of Wuhan University of Technology. Materials science edition, 2018)
First-principles calculations have been carried out to investigate the effects of alloying elements（Zn, Li, Y and Sc） on the electronic structure, elastic and thermal properties of Mg solid solution. The calculated cohesive energies show that Mg-Sc has the highest structural stability. The calculations of the densities of states（DOS） and electronic charge density difference indicate that Mg-Y（Sc） alloys have very strong covalent bonding due to a very strong Mg p-Y（Sc） d hybridization. The bulk modulus B, shear modulus G, Young＇s modulus E and Poisson ratio ν are derived using Voigt-Reuss-Hill（VRH） approximation. The results show that all the alloys can exhibit ductile properties at 2.77 at% R, and Mg-Zn（Li） alloys have the better ductility and plasticity. In the end, the Debye temperature and isochoric heat capacity are also calculated and discussed.